2013
DOI: 10.2105/ajph.2012.300955
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Air Pollution in Developing Countries: Research and Implementation Needs for Improvements in Global Public Health

Abstract: Exposure to indoor air pollution (IAP) from the burning of solid fuels for cooking, heating, and lighting accounts for a significant portion of the global burden of death and disease, and disproportionately affects women and children in developing regions. Clean cookstove campaigns recently received more attention and investment, but their successes might hinge on greater integration of the public health community with a variety of other disciplines. To help guide public health research in alleviating this imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 48 publications
0
43
0
1
Order By: Relevance
“…ETS combined with other IAP, particularly antenatal exposure, affects lung growth that persists through adulthood [97]. There are numerous by-products of combustion; particulate matter (PM), carbon dioxide (CO 2 ), sulfur dioxide (SO 2 ), nitrogen dioxide (NO 2 ), and volatile organic compounds (VOC) are the most commonly assessed by-products of ETS and other combustions [95,98]. Recently it has been shown that sub- and nano-micron particles contribute to adverse effect of PM on the lung health of children [99].…”
Section: Resultsmentioning
confidence: 99%
“…ETS combined with other IAP, particularly antenatal exposure, affects lung growth that persists through adulthood [97]. There are numerous by-products of combustion; particulate matter (PM), carbon dioxide (CO 2 ), sulfur dioxide (SO 2 ), nitrogen dioxide (NO 2 ), and volatile organic compounds (VOC) are the most commonly assessed by-products of ETS and other combustions [95,98]. Recently it has been shown that sub- and nano-micron particles contribute to adverse effect of PM on the lung health of children [99].…”
Section: Resultsmentioning
confidence: 99%
“…COPD is believed to be a combination of disorders, including chronic bronchitis and emphysema, both of which cause diminished airflow at expiration and are associated with obstructed bronchi [1,4,5]. The disease has become a silent killer in low-and middle-income countries because of its slow progression in many patients [6][7][8]. Currently estimated to affect 328 million people worldwide, COPD is expected to become one of the leading causes of death within the next 2 decades, although data from outside the USA and European Union are still limited [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of adoption rates are sparse and the factors that may influence adoption are largely unknown (Lewis and Pattanayak, 2012); there is a significant need for better collaboration between public health officials and researchers to gain clarity on what drives cookstove adoption (Gall et al, 2013). Few studies integrate real-time objective measurements of both air pollution and stove use (Ruiz-Mercado et al, 2011).…”
Section: Introductionmentioning
confidence: 99%